2019
DOI: 10.3390/ijms20071791
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation Differentially Alters the Proteome of Epididymal and Ejaculated Pig Spermatozoa

Abstract: Cryopreservation induces differential remodeling of the proteome in mammalian spermatozoa. How these proteome changes relate to the loss of sperm function during cryopreservation remains unsolved. The present study aimed to clarify this issue evaluating differential changes in the proteome of fresh and frozen-thawed pig spermatozoa retrieved from the cauda epididymis and the ejaculate of the same boars, with clear differences in cryotolerance. Spermatozoa were collected from 10 healthy, sexually mature, and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 57 publications
3
19
0
Order By: Relevance
“…Firstly, the glycosylated form of GM-CSF would be a native protein of spermatozoa derived from spermatogenesis as demonstrated by its presence in the residual bodies released from spermatids during final spermiogenesis. The low relative abundance of this cytokine in spermatozoa would explain why it was not identified in the current pig sperm proteome 44 , 45 , maybe due to the lack of sensitivity of the current methods for proteomics failing to identify low abundant peptides, as it would be the situation for many cytokines 5 . Secondly, this glycosylated form could be inside the SP-extracellular vesicles that are attached to the spermatozoa during ejaculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the glycosylated form of GM-CSF would be a native protein of spermatozoa derived from spermatogenesis as demonstrated by its presence in the residual bodies released from spermatids during final spermiogenesis. The low relative abundance of this cytokine in spermatozoa would explain why it was not identified in the current pig sperm proteome 44 , 45 , maybe due to the lack of sensitivity of the current methods for proteomics failing to identify low abundant peptides, as it would be the situation for many cytokines 5 . Secondly, this glycosylated form could be inside the SP-extracellular vesicles that are attached to the spermatozoa during ejaculation.…”
Section: Discussionmentioning
confidence: 99%
“…A fourth sample, mimicking the EE, was generated by the proportional mixture of the other three portions 10 mL-SRF, rest of SRF and post-SRF as described previously by Perez-Patiño et al . 45 . Each one of four samples were separately centrifuged at 800 × g for 8 min (Eba 20, Hettich Zentrifugen, Germany) immediately after collection to separate spermatozoa from the SP.…”
Section: Methodsmentioning
confidence: 99%
“…The detrimental effects of cryopreservation were immediately observed on TOPAZ1 , M6P/IGF2R , and LOC101123268 after dilution in NC conditions. Changes in the sperm membrane architecture during cryopreservation due to cryodamage caused a protein reorganization, unmasking the expression of some proteins and promoting the loss of other cytoplasmatic or membrane proteins [28,40], which could explain the lower levels of TOPAZ1 , a protein involved in spermatogenesis, and the different levels of those proteins involved in sperm-oocyte interactions ( M6P/IGF2R , LOC101123268 ) in comparison with fresh sperm. According to Belmonte et al [41], M6P/IGF2R might be involved in the recognition of specific glycoconjugates on the zona pellucida, mediating sperm-oocyte interactions and posterior binding.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of these proteins in the reproductive and cryopreservation process still needs to be further characterized. Recently, a deeper proteomics study on a non-ruminant species (boar) showed intriguing results about how variations in the proteome of epididymal and ejaculated sperm could affect the sperm cryotolerance [116]. Many of the differentially abundant proteins between these sperm sources were mainly involved in energy metabolism, structural activity, redox homeostasis, immune response and fertilization.…”
Section: Protein Namementioning
confidence: 99%